2018
DOI: 10.3390/w10121754
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Key Information and Land Management Plans for Water Conservation under Dry Weather Conditions in the Border Areas of the Syr Darya River in Kazakhstan

Abstract: Due to an increase in poorly planned anthropogenic activities, the water quality of several Asian big rivers is highly being affected. Although the assessment of heavy metal contents is vital to develop and design sustainable water management plans, several areas in Central Asia such as Kazakhstan do not have recent studies available that evaluate this situation. One representative example of this lack of information is the Syr Darya River. Thus, this study carried out the first approach to a water quality ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 56 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…It is important to accurately analyze the planktonic algal biomass and taxonomic groups in estuarine ecosystems, to enable evaluation of the biological dynamics of these systems. In addition, since estuaries are strongly influenced by human activities and have a direct impact on the ocean, many researches on aquatic environment have been conducted [5,6]. As the impact of climate change can be clearly identified, a lot of research has recently been conducted between climate change and aquatic ecosystem [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to accurately analyze the planktonic algal biomass and taxonomic groups in estuarine ecosystems, to enable evaluation of the biological dynamics of these systems. In addition, since estuaries are strongly influenced by human activities and have a direct impact on the ocean, many researches on aquatic environment have been conducted [5,6]. As the impact of climate change can be clearly identified, a lot of research has recently been conducted between climate change and aquatic ecosystem [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the connectivity processes, we can be sure that roadside soils will not be an isolated problem [68]. As recently several authors demonstrated in highly populated urban areas, agricultural fields or mining areas, the second most affected source affected by roadside soils is the water [69][70][71][72]. So, it would be interesting to assess for this studied territory, the possible impacts of roadside soils on the nearly water bodies.…”
Section: Evaluation Of Heavy Metals In Soils By Using Indexing Approachmentioning
confidence: 94%
“…Although the assessment of heavy metal contents is vital to develop and design sustainable water management plans, several areas in Central Asia such as Kazakhstan do not have recent studies available that evaluate this situation. Yegemova et al [15] identified the key information and land management plans for water conservation under dry weather conditions in the border areas of the Syr Darya River in Kazakhstan. These authors carried out the first approach to a water quality assessment in Kazakhstan's Syr Darya River, where a massive expansion of irrigation canals, pastures in middle-and lower-reaches and an increase in industrialization and population have lowered its potential water capacity.…”
Section: Land Uses Tillage Practices and Water Qualitymentioning
confidence: 99%